THE INFLUENCE OF DISTRIBUTION COST AND PROMOTION COST TO SALES VOLUME OF CANDY TOLAK ANGIN IN PT MUNCUL MEKAR SEMARANG - Arindra Diesnu Hernomo; Apriatni Endang Prihatini; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2012)
This study about the influence of distribution cost and promotion cost to sales volume of candy tolak angin  in PT Muncul Mekar Semarang. Companies often experience fluctuations in sales volumes of  candy tolak angin. Issues to be discussed is how the promotion cost influence to sales volume, how the distribution cost influence to sales volume as well as how the influence of promotion costs and distribution costs to sales volume. While the purpose of this study is to determine the influence of promotion costs to sales volume, the influence of distribution costs to sales volume and the influence of promotion costs and distribution costs to sales volume. The type of this study is explanatory research that is explained and research the influence of existing variables. The data used is data in period of 2006 to 2011. To get it is used interview techniques to related parties. From the statistical calculations using simple regression analysis was known promotion costs to sales volume Y= 5222,9 + 0,0000193 X1, distribution costs to sales volume Y = 5638,8+  0,00007478 X2. Through the multiple regression analysis between the cost of promotion and distribution costs to sales volume Y = 5044,6+  0,0000195 X1 +  0,0000904 X2. By using the F test is known that the value of F count is 18.2 greater than F table (df1 = k= 2 and df2 = n-k-1=72-2-1 = 69) so F table is 3.13. And obtained the values ​​of significance (P value) is 0.001. Since the value of P value less than 0.05 it  means Ha is accepted and Ho rejected, so it can be concluded that the promotion costs and distribution costs together may influence sales volume. While the dominant influence is given by the promotion costs. The conclusion is that the promotion costs used to support promotional activities are appropriate because the promotion is interesting.